Increasing the Stimulation Dose of rFSH in Unexpected Poor Responders Is Not Associated with Better IVF Outcome - Levent Tutuncu; Ozgur Dundar (The Scientific World Journal)
The aim of this retrospective study is to determine whether increasing the stimulation dose of rFSH in unexpected poor responders is associated with better in vitro fertilization (IVF) outcome or not. A total of forty eligible women who fulfilled our definition of poor responders and who did not achieve an ongoing pregnancy in the first cycle and returned for a second higher rFSH dose IVF cycle with a long-agonist protocol were included to the study. The first low-dose cycles and the second high-dose cycles were compared to each other. Main outcome measures of the study were duration of stimulation, number of follicles, number of oocytes retrieved, number of embryos, and E2 level on day of hCG injection. There were no significant differences in duration of stimulation, number of follicles, number of oocytes retrieved, number of embryos, and E2 level on day of hCG injection between the first low- and second high-dose cycles. Daily dose and total dose of rFSH were significantly higher in the second high-dose cycles. Increasing the dose of rFSH in a second stimulation cycle after first unsuccessful treatment cycle will add only to the cost and discomfort of the treatment and might adversely affect pregnancy rates.